Two-stage anaerobic digestion for hydrogen and methane production - Ribeiro, Alexandre Rodrigues; Devens, Kauanna Uyara; de Freitas, José Arnaldo; Batista, Lia Paula Poloni; Albanez, Roberta; Lovato, Giovanna; Rodrigues, José Alberto Domingues [UNESP]; Silva, Edson Luiz (Elsevier, 2025)
Anaerobic digestion is increasingly recognized as an important alternative for organic wastewater treatment, enabling the production of bioenergy and value-added compounds, while ensuring the environmental suitability of waste. The single-stage configuration, in which the acidogenic and methanogenic phases occur in a single reactor, and the two-stage configuration, in which these phases occur in different reactors, are analyzed focusing on the importance of anaerobic digestion for implementing the circular economy, offering economic benefits, energy efficiency and environmental advantages, considering both operational aspects of the process and fundamental aspects of molecular microbiology and mathematical modeling, aiming for large-scale applications.